2007
DOI: 10.1095/biolreprod.106.058578
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dietary Fatty Acids on Oocyte Quality and Development in Lactating Dairy Cows1

Abstract: The purpose of this study was to examine the effects of level of rumen inert fatty acids on developmental competence of oocytes in lactating dairy cows. Estrous cycles were synchronized in 22 cows on a silage-based diet supplemented with either low (200 g/day) or high (800 g/day) fat. A total of 1051 oocytes were collected by ultrasound-guided ovum pickup (OPU) in seven sessions/cow at 3-4 day intervals. Oocytes were matured, fertilized, and cultured to the blastocyst stage in vitro. Embryo quality was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
0
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(119 citation statements)
references
References 67 publications
8
100
0
11
Order By: Relevance
“…Regarding the effects of feed supplementation on oocyte quality, the literature data are controversial. Many of the studies indicate that increasing the amount of energy in diets for beef and dairy cows and heifers produces deleterious effects on oocyte competence and embryo quality (Armstrong et al, 2001;McCaffery et al, 2000;Nolan et al, 1998;Freret et al, 2006); other studies have shown beneficial effects of supplementation and fat (Fouladi-Nashta et al, 2007). However, most studies disregard the effects of the initial body condition of the animals or their overconditioning as for the response of the yield and quality of oocytes and embryos.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the effects of feed supplementation on oocyte quality, the literature data are controversial. Many of the studies indicate that increasing the amount of energy in diets for beef and dairy cows and heifers produces deleterious effects on oocyte competence and embryo quality (Armstrong et al, 2001;McCaffery et al, 2000;Nolan et al, 1998;Freret et al, 2006); other studies have shown beneficial effects of supplementation and fat (Fouladi-Nashta et al, 2007). However, most studies disregard the effects of the initial body condition of the animals or their overconditioning as for the response of the yield and quality of oocytes and embryos.…”
Section: Resultsmentioning
confidence: 99%
“…Gong et al (2002) found, at equal levels of milk production and energy balance, that the increased insulin from a glucogenic diet significantly increased the proportion of cows ovulating at 50 days postpartum. However, there is also evidence that high concentration of blood insulin has negative effects on oocyte quality (Fouladi-Nashta et al, 2005). These observations led to the proposal of a strategy of glucogenic feeding to give a high insulin level and thereby reduce the length of the postpartum anoestrus, followed by more lipogenic feeding to lower insulin levels and improve oocyte developmental quality (Garnsworthy et al, 2008c).…”
Section: Glucogenic-lipogenic Feeding Sequencesmentioning
confidence: 99%
“…In this context, dietary fat supplementation increases the size and estradiol secreting capacity of pre-ovulatory follicles and provides the substrates for enhanced progesterone secretion (Leroy et al, 2008b). Lipogenic diets may reduce insulin (Garnsworthy et al, 2008b) as well as improving blastocyst development rate (Fouladi-Nashta et al, 2007). Using synchronised multiparous Holstein cows (n 5 30), Garnsworthy et al (2008a) showed that glucogenic diets tended to be detrimental for oocyte quality.…”
Section: Glucogenic-lipogenic Feeding Sequencesmentioning
confidence: 99%
“…Moreover, in these animals, there was an increase in the proportion of long-chain fatty acids in the plasma and cumulus cells (Zeron et al, 2002). In dairy cows, another study has shown that a diet enriched in a mixture of saturated and unsaturated fats affected oocyte development and maturation (Fouladi-Nashta et al, 2007). The two fatty acids linoleic acid (LA) and linolenic acid (ALA) are both found in the plasma and follicular fluid of cows (Childs et al, 2008), and it has been reported that supplementation of bovine oocytes with ALA during IVM resulted in an increased maturation rate, a higher yield of blastocysts and the production of better-quality blastocysts (Marei et al, 2009).…”
Section: Nefasmentioning
confidence: 97%